Mosca-Negra-dos-Citros: Características Gerais, Bioecologia e Métodos de Controle dessa Importante Praga Quarentenária da Citricultura Brasileira - da Silva, Anderson Goncalves; Farias, Paulo Roberto Silva; Boica Junior, Arlindo Leal Boica; Souza, Bruno Henrique Sardinha (My University, 2011)
Citrus blackfly, Aleurocanthus woglumi Ashby, is a serious pest of citrus culture and other economically important fruit crops. It is a present quarantine pest or A2 maximum alert restricting trades with other regions free of its presence. Since the frst occurrence of the citrus blackfly in Belem in 2001 its dissemination was quickly to other States and regions of citrus production in Brazil. As an exotic pest, basic knowledge is scarce in order to establish the appropriate management to the insect in Brazil. Thus, the aim of the present study was to provide information about important aspects of A. woglumi, such as: history and geographical distribution, bioecology, host plants, appropriate control methods, among others, in order to provide subsidies for futures researches about the citrus blackfly in Brazil.
Citrus Blackfly: General Aspects, Bioecology and Methods for the Control of this Important Quarantine Pest to Brazilian Citrus Production.